International Competitiveness of China - Loo, Yoke Mei (2007)
This paper evaluates contributory factors responsible for the competitiveness of China in relation to the world’s economy. Over the past few years, China has been successful in attracting massive Foreign Direct Investment (FDI) into the country. China’s phenomenal success was further magnified when the country joined the membership of World Trade Organisation (WTO) in year 2001 encouraging exports performance of the country and further spurring the growth of the country. The phenomenal success of China’s economic improvement was said to have stem from the availability of cheap labour workforce. This study intends to demonstrate that Chinese competitiveness does not only limit itself to the cheap labour, but also other macro factors that could affect the competitiveness of the country such as foreign investments, human capital, physical capital, market potential, productivity and the accession of China into WTO. Investigation on the impact of various factors at ‘aggregate’ level mentioned above will be done using unit root test and multivariate cointegration tests. Results from the empirical reveal that FDI and the accession of China into WTO played a significant role in enhancing the competitiveness of China. In short-run, it was found that both factors act as a catalyst in generating long-term competitiveness of China’s export per se. The openness of China’s trade and investment tends to stimulate the spillovers of capitals, hence allowing sufficient technologies, knowledge and skills to be absorbed. These factors in turn prepare the economy of the country to adjust necessarily to maintain its competitiveness in long-term.